Cytokine release syndrome and cancer immunotherapies – historical challenges and promising futures - Shah, Deep; Soper, Brian; Shopland, Lindsay (Frontiers in Immunology, 2023)
Cancer is the leading cause of death worldwide. Cancer immunotherapy involves reinvigorating the patient’s own immune system to fight against cancer. While novel approaches like Chimeric Antigen Receptor (CAR) T cells, bispecific T cell engagers, and immune checkpoint inhibitors have shown promising efficacy, Cytokine Release Syndrome (CRS) is a serious adverse effect and remains a major concern. CRS is a phenomenon of immune hyperactivation that results in excessive cytokine secretion, and if left unchecked, it may lead to multi-organ failure and death. Here we review the pathophysiology of CRS, its occurrence and management in the context of cancer immunotherapy, and the screening approaches that can be used to assess CRS and de-risk drug discovery earlier in the clinical setting with more predictive pre-clinical data. Furthermore, the review also sheds light on the potential immunotherapeutic approaches that can be used to overcome CRS associated with T cell activation.